La Mystérieuse flamme de la reine Loana et l’espace vide de l’individuel - Patrizia Violi (Cahiers de Narratologie)
The aim of this text is to discuss some problematic aspects of Umberto Eco’s theoretic elaboration, in particular the notions of subjectivity and individuality, rereading his more autobiographic novel The mysterious Flame of Queen Loana. The novel is paralleled with Eco’s theory of subjectivity, showing how some problematic issues at the theoretical level are dealt with only in his fictional writing.